Effects of low-level laser therapy on the proliferation and apoptosis of gingival fibroblasts treated with zoledronic acid - Pansani, Taisa Nogueira; Basso, Fernanda Gonçalves [UNESP]; Turrioni, Ana Paula Silveira; Kurachi, C.; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza (Churchill Livingstone, 2014)
Low-level laser therapy (LLLT) has been indicated as an adjuvant therapy for bisphosphonate-induced osteonecrosis. However, the effects of LLLT on bisphosphonate-treated cells are not yet clear. This study evaluated the effects of LLLT on the proliferation and apoptosis of gingival fibroblasts treated with zoledronic acid (ZA). Cells were exposed to ZA at 5 mu M for 48 h. Irradiation was performed using a laser diode prototype (LaserTABLE, InGaAsP; 780 nm +/- 3 nm, 25 mW) at 0.5 or 3 J/cm(2), three times every 24 h. Cell proliferation and apoptosis were evaluated by fluorescence microscopy. Data were analyzed by Mann-Whitney test at the 5% level of significance. ZA decreased cell proliferation to 47.62% (interquartile range (IQR) 23.80-57.14%; P = 0.007) and increased apoptosis of gingival fibroblasts to 27.7% (IQR 20.9-33.4%; P = 0.0001). LLLT increased cell proliferation compared with non-irradiated cells, at 0.5 J/cm(2) (57.14%, IQR 57.14-71.43%; P = 0.003) and at 3 J/cm(2) (76.19%, IQR 61.90-76.19%; P = 0.0001), but did not increase cell proliferation in ZA-treated cells. Irradiated fibroblasts presented lower apoptosis rates than the ZA-treated cells, but apoptosis was no different in ZA-treated cells compared to those that were ZA-treated and also irradiated.
Keywords: bisphosphonates; cell culture; cell death; cell division; osteonecrosis; laser therapy; zoledronic acid-treated cells